2006
DOI: 10.1063/1.2185407
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast recombination in Si-doped InN

Abstract: We report femtosecond near-infrared transient photoreflection measurements of native n-type indium nitride and silicon-doped indium nitride thin films. The overall time dependence of the ultrafast reflectivity transient is characterized by the different time scales of carrier cooling and carrier recombination. Experimental analysis demonstrates nonradiative recombination in the picosecond and subpicosecond range as the dominant recombination mechanism at room temperature even at very high carrier concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…These features allowed us to suggest a trap-assisted Auger recombination being the dominant recombination mechanism in InN. The modelling provided a value of trap-assisted Auger recombination coefficient B * = C TAA N T = 8×10 [6]. As for the PL study [5], the Auger contribution was found only in the early stage of PL decay (i.e.…”
mentioning
confidence: 87%
“…These features allowed us to suggest a trap-assisted Auger recombination being the dominant recombination mechanism in InN. The modelling provided a value of trap-assisted Auger recombination coefficient B * = C TAA N T = 8×10 [6]. As for the PL study [5], the Auger contribution was found only in the early stage of PL decay (i.e.…”
mentioning
confidence: 87%
“…29,79) So far, a wide range of PL lifetimes or carrier lifetimes of sub-ps to a few ns has been reported. [79][80][81][82][83] The main carrier decay process was attributed to NRR at defects rather than Auger processes in Refs. 80 and 82.…”
Section: Luminescence Intensity and Nonradiative Carrier Recombinatiomentioning
confidence: 99%
“…Thus, NRR accompanied by phonon emission is thought to be the dominant recombination Carrier density (cm ) -3 [Mg] (cm ) process. 81) In spite of the research on NRR centers, there is little information on the elemental NRR processes. Figure 11 shows the LO phonon energy and the difference between the inverse values of the two dielectric constants at the high frequency limit and low-frequency limit.…”
Section: ¹1mentioning
confidence: 99%
“…Amplitude of this transient is linear with the pump fluence indicating that it is a density-dependant process. A similar transient has been observed in differential reflection measurements [3] and ascribed to the band gap renormalisation presuming that the band filling is far from saturation at short delays and high carrier temperature, so it cannot be responsible for the rapid change in the signal. The fast transient is followed by a build-up of the "main" signal.…”
Section: Samples and Experimental Techniquementioning
confidence: 61%
“…Among others, carrier thermalisation rate, lifetime, diffusion coefficient are of great importance for device design and operation. Optical pump-probe techniques like time-resolved differential transmission (DT) and reflection are well-suited for the investigation of carrier dynamics and have been widely applied over past years [1][2][3]. However, the mechanisms determining the carrier lifetime and its dependence on excitation fluence are not well understood and require further analysis.…”
Section: Introductionmentioning
confidence: 99%